Evaluate the efficiency of treatment by using electromagnetic field in reducing bacterial contamination in wells water - Mohammed Gh. Farhan; Jihad D. Mahal; Awaz B. Mohammed (Tikrit Journal of Pure Science)
This study was conducted on nine wells water within Kirkuk city for the period  1st July 2015 until 13th June 2016 to assess the electromagnetic field's effectiveness in groundwater purification, where the study focused on the design apparatus with different electromagnetic fields accomplished by exposing the water to electromagnetic fields while the water is passing through the device. Electromagnetic water treatment  process consists of  two phases , the first  by using different electromagnetic fields 1.4,1.7,1.9 Tesla with the stability of the water passage time 20 minutes through electromagnetic field and the second phase is consists of fixed electromagnetic field intensity 1.9 Tesla with change water retention time 5, 10, 20 minutes during the electromagnetic field. Study showed the effect of electromagnetic treatment on bacterial pollution indicators (total number of aerobic bacteria and total coliform bacteria) the number of bacteria colonies decreased at a rate of 90% at a field intensity  1.9 Tesla and to  93% at a retention time 20 minutes, as the coliform bacteria  decreased at a rate of 94% when field intensity 1.9 Tesla ,and [98thvd retention time 20 minutes